Fatigue response of friction stir welded joints of Al 6061 in the absence and presence of inserted copper foils in the butt weld. (April 2021) - Hassanifard, S.; Alipour, H.; Ghiasvand, A.; Varvani-Farahani, A.
Abstract: The present study examines the impact of inserted copper foil on n mechanical characteristics and fatigue strength of aluminum 6061 butt joints welded through the Friction Stir Welding (FSW) process. Thin copper foils were inserted between the faying surfaces of the sheet joints alloying Al 6061 locally with copper foil over FSW operation. Test specimens were then cut off from the welded plates to examine the quasi-static and fatigue behavior of the joints. The load-controlled condition tests were conducted on the specimens with a stress ratio of R = 0.1. Insertion of copper foils of 100 μ m and 200 μ m in the stirred zones, improved tensile strengths respectively 48 % and 31 %. The fatigue life of alloyed joints was improved as compared to as-welded joints in the absence of foils. A three-dimensional finite element (FE) analysis was employed to simulate the maximum stress and strain values in the weld zones. Weld regions due to their different mechanical properties experienced different stress magnitudes. The simulated stress and strain components were then used to predict uniaxial fatigue lives of FSW joint samples through the Smith-Watson-Topper (SWT) approach.